Fission track and U-Pb in situ dating applied to detrital zircon from the Vale do Rio do Peixe Formation, Bauru Group, Brazil - Dias, A. N. C. [UNESP]; Tello, C. A. S. [UNESP]; Chemale, F.; de Godoy, M. C. T. F. [UNESP]; Guadagnin, F.; Iunes, P. J.; Soares, C. J. [UNESP]; Osorio, A. M. A. [UNESP]; Bruckmann, M. P. (Pergamon-Elsevier B.V. Ltd, 2011)
Combined methods of fission track (FTM) and U-Pb in situ zircon dating were applied to sedimentary samples from the Vale do Rio do Peixe Formation, Bauru Basin, Brazil. Detrital zircons of nine samples were determined by the FTM, and the obtained ages varied from 239 Ma-825 Ma, which can be grouped into four main populations as the 230-300 Ma, 460-490 Ma, 500-650 Ma and 696-825 Ma groups. The U-Pb data show two clear source areas: the Early Paleozoic to Neoproterozoic zircons, ranging from 445 +/- 14 to 708 +/- 18 Ma, and the Paleoproterozoic zircons, ranging from 1879 +/- 23 to 2085 +/- 27 Ma. Subordinate occurrences of Early Neoproterozoic to Mesoproterozoic zircons (836 +/- 15 and 1780 +/- 38 Ma) were identified. The combined information allows us to characterize Early Brazilian, Brazilian and Rhyacian material as the main source for the zircons, which are areas situated to west of the Bauru Basin (e.g., Goias Massif) that have been incorporated into the sedimentary cycles in the Phanerozoic (mainly in the Parana Basin). FT zircon ages reflect the main denudation processes of the South American Plate from Neoproterozoic to Early Triassic as those related to orogenic cycles of Early Brazilian, Brazilian, Famatinian/Cuyanian and Gondwanide. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Zircon fission track; U-Pb in situ dating; Vale do Rio do Peixe Formation; Bauru Group